Penggunaan Metode Pembelajaran Talking Stick untuk Meningkatkan Keterampilan Berbicara Peserta Didik Kelas X G SMA Negeri 5 Kupang - Jelalu, Quirinus; Djuli, Labu; Lakapu, Imanuel (Jurnal Lazuardi, 2024)
By using the Kemmis and Taggart model, this research aims to find out how much influence the use of the Talking Stick learning method has on the speaking skills of Class X G students at SMA Negeri 5 Kupang. Classroom action research consists of 4 phases, namely planning, implementation, observation, and reflection. This research was conducted on 36 Class X G students at SMA Negeri 5 Kupang. All data is collected through interviews, written tests, and observations. The research results showed a significant increase in identifying themes and atmosphere in poetry after using the Talking Stick method. In the initial condition, students' speaking skills were ≤50%, cycle 1 activities reached an average of 55% with an increase of 5%. Therefore, researchers made improvements to cycle 2 activities reaching an average of 85%. Based on the comparison table of learning results, it shows that there was an increase after carrying out cycle 1 activities, resulting in Classical Learning Completeness (KBK) of 62%. Therefore, the researchers made improvements to cycle 2 activities to obtain Classical Learning Completeness (KBK) of 100% with an increase of 38% from cycle 2. The increase in learning outcomes was influenced by the use of the Talking Stick method which is very suitable for application in Indonesian Language Subjects. so that it is easy to understand the material and can improve speaking skills, create activity in the intellectual aspects, attitudes and motor skills of students. Keywords: Talking Stick Method, Speaking Skills, Poetry, Classroom Action Research.